2014
DOI: 10.5047/meep.2014.00201.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Sea of Japan and Its Unique Chemistry Revealed by Time-Series Observations over the Last 30 Years

Abstract: Chemical tracers in seawater, as well as physical parameters such as temperature and salinity, have been measured to better characterize the dynamics of water convection and its spatiotemporal changes in the Sea of Japan (also called the Japan Sea), a semi-closed, hyperoxic marginal sea (maximum depth: ∼3,800 m) in the northwestern corner of the Pacific Ocean. Repeated conductivity, temperature, and depth (CTD) observations and measurements of dissolved oxygen, for more than 30 years, have confirmed that the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 75 publications
4
38
0
Order By: Relevance
“…Salinity and nutrient in the TWC is controlled by the circulation in the East China Sea and the Yangtze discharge which could be controlled by precipitation over South China during the East Asian summer monsoon season. The deep water circulation in the Japan Sea is characterized by intense ventilation due to severe cooling during winter monsoon season, which promotes the hyper-oxic deep water condition and shallow carbonate compensation depth of the sea (Gamo et al 2014). The Japan Sea is also located at downwind of the Asian dust sources and receives a significant amount of dust transported by westerlies in spring or northwestern monsoon wind in winter Tada 2000, 2002).…”
Section: Drilled Sitesmentioning
confidence: 99%
“…Salinity and nutrient in the TWC is controlled by the circulation in the East China Sea and the Yangtze discharge which could be controlled by precipitation over South China during the East Asian summer monsoon season. The deep water circulation in the Japan Sea is characterized by intense ventilation due to severe cooling during winter monsoon season, which promotes the hyper-oxic deep water condition and shallow carbonate compensation depth of the sea (Gamo et al 2014). The Japan Sea is also located at downwind of the Asian dust sources and receives a significant amount of dust transported by westerlies in spring or northwestern monsoon wind in winter Tada 2000, 2002).…”
Section: Drilled Sitesmentioning
confidence: 99%
“…Convection and formation of deepwater caused by dry and cold winds are reported for the Japan Sea [e.g., Nitani , ; Gamo and Horibe , ; Sudo , ; Gamo , ], which is similar to that observed for the global conveyor belt in the world's oceans [ Broecker , ]. For these reasons, the Japan Sea, although being a marginal body of water, has been referred as a “Miniature Ocean” [e.g., Gamo et al ., ], that can serve as a model for the world's oceans.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japan Sea, very homogeneous water exists at depth of below a few-hundred meters. This water mass, which is called the ''Japan Sea Proper Water,'' has extremely narrow range of water temperature (0.0-0.68C) and salinity (34.06-34.08), and is highly oxygenated (0.2-0.23 mM) [e.g., Uda, 1934;Yasui et al, 1967;Gamo et al, 2014]. Convection and formation of deepwater caused by dry and cold winds are reported for the Japan Sea [e.g., Nitani, 1972;Gamo and Horibe, 1983;Sudo, 1986;Gamo, 1999], which is similar to that observed for the global conveyor belt in the world's oceans [Broecker, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Recent oceanographic observations revealed that the gradual deoxygenation and warming of the bottom water of the East Sea over the last 30 years have resulted in an ∼ 10 % decrease in dissolved oxygen and ∼ 0.04 • C increase in potential temperature (Kim et al, 2001;Gamo, 2011;Gamo et al, 2014). Benthic metabolism and respiratory C org oxidation coupled to various terminal electron-accepting processes in the sediments are largely controlled by the combination of O 2 content, temperature, and biological production overlying the water column (Canfield et al, 2005).…”
Section: The Ub As a Biogeochemical Hotspotmentioning
confidence: 99%